Antibodies affecting ion channel function in acquired neuromyotonia, in seropositive and seronegative myasthenia gravis, and in antibody-mediated arthrogryposis multiplex congenita. - Vincent, A; Jacobson, L; Plested, P; Polizzi, A; Tang, T; Riemersma, S; Newland, C; Ghorazian, S; Farrar, J; MacLennan, C; Willcox, N; Beeson, D; et al. (1998)
A new autoimmune disease affecting the neuromuscular junction has been defined. Acquired neuromyotonia is associated with antibodies to voltage-gated potassium channels that act, at least in part, by reducing potassium channel function with resulting neuronal hyperactivity. This condition is quite frequently associated with thymoma and, in many cases, antibodies to acetylcholine receptors are present as well as antibodies to VGKC. Improvements in techniques and the availability of cloned DNA and recombinant forms of the AChR subunits have led to new observations concerning the specificity and roles of antibodies in myasthenia gravis. The transfection of a cell line with the epsilon subunit means that we can now accurately compare antibodies reactive with adult and fetal human AChR. This may help to determine the relationship between AChR subunit expression in different tissues and the induction of antibodies that bind specifically to the two forms, as well as to clarify the role of antibodies to fetal or adult AChR in causing ocular muscle symptoms. Serum antibodies from a few mothers with obstetric histories of recurrent arthrogryposis multiplex congenita in their babies specifically inhibit the function of fetal AChR. These observations not only explain the cause of some cases of arthrogryposis multiplex congenita, but also suggest that other fetal-specific antibodies might be responsible for other fetal or neonatal conditions. An animal model has been established to enable us to investigate the role of maternal serum factors in causing such disorders. Seronegative MG has been the subject of many studies from our laboratory over the last ten years. The transience of the effects of SNMG plasmas on AChR function strongly suggests that the plasma antibodies do not bind directly to the AChR, but inhibit function by some indirect mechanism. They do not appear to act via the cAMP-dependent protein kinase pathway, and studies are in progress to investigate the involvement of other second messenger systems.